Distribution of Micropogonias furnieri (Pisces: Sciaenidae) in the Sepetiba Bay, Rio de Janeiro, Brazil - Rodriguez da Costa, M.=700 1 Gerson Araujo, F.
(Es, En)
ilus., 9 ref.
Keywords: ECOLOGIA MARINA; ECOLOGIA ANIMAL; DISTRIBUCION GEOGRAFICA; PECES; BRASIL